Advanced approach to the local structure reconstruction and theory validation on the example of the W L3-edge extended x-ray absorption fine structure of tungsten. (5th January 2018) - Jonane, Inga; Anspoks, Andris; Kuzmin, Alexei
Abstract: Atomistic simulations of the experimental W L3 -edge extended x-ray absorption fine structure (EXAFS) of bcc tungsten at T = 300 K were performed using classical molecular dynamics (MD) and reverse Monte Carlo (RMC) methods. The MD-EXAFS method based on the results of MD simulations allowed us to access the structural information, encoded in EXAFS, beyond the first coordination shell and to validate the accuracy of two interaction potential models—the embedded atom model potential and the second nearest-neighbor modified embedded atom method potential. The RMC-EXAFS method was used for more elaborate analysis of the EXAFS data giving access to thermal disorder effects. The results of both methods suggest that the correlation in atomic motion in bcc tungsten becomes negligible above 8 Å. This fact allowed us to use the EXAFS data to determine not only mean-square relative displacements of atomic W–W pair motion but also mean-square displacements of individual tungsten atoms, which are usually accessible from diffraction data only.